INFLUENCE OF MECHANICAL DEFORMATION ON PHOTOSENSITIVITY PROPERTIES OF THIN SEMICONDUCTOR FILMS - Siddiqov Rustamjon O’ktamovich (American Journals, 2023)
The article presents arguments about the influence of mechanical deformation on the photosensitivity properties of thin semiconductor films.
Keywords: photosensitivity, semiconductor film, phototensor, deformation, tension, compression.